(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2018)
This research aims to apply the control and supervision of banking in accordance with the standards and rules issued by the Central Bank and the importance of the role played by these standards and impacts on the banking institutions and is banking supervision of the most important requirements for the continuation of the banking business, which needs to have a supervisory awareness of the bank in order to provide banking services efficiently and comes oversight role oversight by the central bank through banks control by laws and regulations and knowledge of its role in achieving financial stability